SIGNIFICANCE AND APPLICATION OF THE GREEN PRACTICE CONCEPT IN HOSPITALITY INDUSTRY IN NOVI SAD - Šmugović, Stefan; Kalenjuk, Bojana M; Knežević , Natalija; Živković , Nikola (The Business of Tourism, 2021)
The application of the green practice in hospitality is becoming more widespread and the awareness of its importance is growing every day. As hospitality belongs to the industry that uses different materials, energy sources and generates different types of waste, the concept of green restaurants is a good sustainable solution for this type of problem that affects the environment. Green restaurants have a great opportunity and chance to create a competitive advantage and thus improves the corporate image, through a more efficient environmental policy and reducing operating costs. The subject of this paper is the importance and application of the concept of green practice in restaurant facilities. The task of the paper is to examine the employees of hospitality facilities on the territory of Novi Sad with the aim of researching the awareness among the employees about the importance of green restaurants and knowledge about them and the advantages they can achieve.
Keywords: green practice; sustainable business; green restaurants; hospitality